A New Act East Approach: Revisiting INDO-ASEAN Relations via Northeast Window - Khaki, Hina Hassan (International Research Journal of Management, IT & Social Sciences, 2016)
The idea envisaged under the Look East Policy was to interact and build relationships with our immediate strategic neighbourhood in the east, namely Myanmar, Bangladesh, Vietnam, Laos, Cambodia and Thailand. It was believed that trade with the neighbouring countries would resurrect the economies of the border-states in the region, bringing peace and stability. The objective of the policy predominantly focuses on the regional economic integration with renewed emphasis on the development of the North East Region of India. Most recently, development of the North Eastern Region has been the need of the hour and the Look East Policy for the advancement of the Region is Initiating a number of substantive endeavours. One among the several geostrategic imperatives that necessitate the development of North East Region is the border it shares with Myanmar. It was perceived if ASEAN was gateway to wider Asia Pacific Region, Myanmar was a land bridge to ASEAN and North East Region the gateway to Myanmar. In spite of being at a congenial geographic location to grasp the benefits from Indo-ASEAN cooperation the North East Region is cited as one of the remote landlocked regions of vibrant Indian Economy that has miserably failed to taste the fruits of development. This paper discusses how Look East Policy is fundamentally induced to diminish Indiaâs internal development disparity by promoting the significance of the North east as gateway to east; to critically analyse the reasons for major disconnect between Look East Policyâs vision and ground realities so far as north east is concerned and to devise possible policy solutions for greater engagement and development of the region so that it will not remain just a corridor.